Storytelling and development of the adult storyteller (Práxis Educativa, 2019)
This study seeks to understand how storytelling relates to the cognitive and affective development of adult storytellers. It is an exploratory qualitative study based on semi-structured interviews with 30 storytellers and a focus group. The data were analyzed considering the identification of categories according to the clinical method (DELVAL, 2002). The analysis allowed to establish the following categories: passion for reading, listening and telling stories; commitment to the activity; recognition of otherness; affectivity in the process; gratitude and personal transformation. There are indications of improvement in the cognitive and affective aspects of the storyteller. The participants observed a constant affective development from the practice, attributing to the storytelling the changes in the way they acted, behaved and saw the world, getting closer to the human “being” and all his/her fragilities.Keywords: Storytelling. Development. Affectivity. Cognition. Adult.